Patrimonios vivos: diálogo intercultural y defensa territorial en la formación de peritos comunitarios en Ecuador (Tema Central) - Gálvez Mancilla, Elena (2025)
This article analyzes an intercultural pedagogical experience: the course “Community Expertise and Other Forms of Knowledge in the Protection of Natural and Cultural Heritage,” held in 2024 and aimed at members of Indigenous and rural communities whose territories are in conflict with extractive industries. The course brought together students from diverse geographical and ethnic backgrounds, challenging the traditional conception of heritage as an inert object and instead proposing a perspective that integrates nature and culture as living and relational subjects. The methodology was grounded in the recognition of territorial and epistemic diversity, incorporating ancestral knowledge systems. The findings suggest that heritage should be understood as a dynamic web of relationships, where expertise does not reside exclusively in academic institutions but in those who inhabit and care for their territories. Moreover, the course highlighted the tensions between the constitutional recognition of the Rights of Nature and the extractivist policies of the State. This underscores the need to develop new territorial defense strategies that integrate situated knowledge and community-based perspectives.